Eksistensi Kesenian Kuda Lumping di Desa Bandarejo Kabupaten Pasaman Barat - Tiara Natasya; Wimbrayardi Wimbrayardi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe the use, form of presentation and function of the Kuda Lumping art in Bandarejo Village and identify the factors that affect the existence of Kuda art and formulate efforts that can be made to maintain the existence of Kuda Lumping art in Bandarejo Village. This type of research is qualitative research with a descriptive method of analysis. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps to analyze data are data collection, data reduction, data presentation and conclusion drawn. The results of the study show that Kuda Lumping is a Javanese traditional art that still exists in Nagari Lingkuang Aua Bandarejo, West Pasaman Regency. Until now, the art of Kuda Lumping is still performed on the commemoration of the Eid al-Fitr celebration in the area. The art of Kuda Lumping has become a necessity for the people of Nagari Lingkuang Aua Bandarejo, because from the past until now the art of Kuda Lumping is still used and performed in commemoration of big days, especially during the celebration of Eid al-Fitr and the art of Kuda Lumping is still recognized in the midst of the community, so that the existence of the art of Kuda Lumping is still maintained by the community that supports it.